Red blood cell distribution width and the risk of cardiovascular morbidity and all-cause mortality - Arbel, Yaron; Weitzman, Dahlia; Raz, Raanan; Steinvil, Arie; Zeltser, David; Berliner, Shlomo; Chodick, Gabriel; Shalev, Varda (Thrombosis and Haemostasis, 2014)
Red blood cell distribution width (RDW) has been shown to predict cardiovascular mortality in various populations, but studies were less conclusive regarding cardiovascular morbidity. We aimed at evaluating the prognostic effect of RDW on cardiovascular morbidity and allcause mortality in the largest community cohort to date. We utilised the computerised database of a large community based healthcare maintenance organization (HMO) in Israel to identify a cohort of 225,006 eligible patients aged 40 or above who performed a blood count during 2006. We evaluated the relationship between 1% increments of RDW values and major cardiovascular events and all-cause mortality over a period of five years. A total of 21,939 incident cases of a major cardiovascular event and 4,287 deaths were documented during a total of six years of follow up, respectively. In comparison with patients with RDW level <13%, the hazard ratio for total mortality gradually increased to 4.57 (95% confidence interval [CI]: 3.35–6.24, p<0.001) among male patients and to 3.26 (95% CI: 2.49–4.28, p<0.001) among female patients with a RDW of 17% or above. Similar results were evident in anaemic and non-anaemic populations. RDW above 17% was also associated with a modest increased risk of major cardiovascular events in females 1.26 (95% CI: 1.03–1.52, p=0.021), while in men it was not significant, 1.08 (95% CI: 0.82–1.41, p=NS). In conclusion, increasing RDW levels significantly increased risk of cardiovascular morbidity and all-cause mortality. Our observation is evident in both anaemic and non-anaemic patients.
Keywords: RDW; community cohort; major cardiovascular events; total mortality